First Report of Integrative Conjugative Elements in Riemerella anatipestifer Isolates From Ducks in China - Zhu, Dekang; Wan, Jianbang; Yang, Zhishuang; Xu, Jinge; Wang, Mingshu; Jia, Renyong; Chen, Shun; Liu, Mafeng; Zhao, Xinxin; Yang, Qiao; Wu, Ying; Zhang, Shaqiu; et al. (Frontiers in Veterinary Science, 2019)
We report for the first time the occurrence of integrative conjugative elements (ICEs) in Riemerella anatipestifer (R.anatipestifer) isolated from diseased ducks in China. For this purpose, a total of 48 genome sequences were investigated, which comprised 30 publicly available R. anatipestifer genome sequences, and 18 clinical isolates genomes sequences. Two ICEs, named ICERanRCAD0133-1 and ICERanRCAD0179-1 following the classic nomenclature system, were identified in R. anatipestifer through the use of bioinformatics tools. Comparative analysis revealed that three ICEs in Ornithobacterium rhinotracheale showed a high degree of conservation with the core genes of ICERanRCAD0133-1, while thirteen ICEs with high similarity to ICERanRCAD0179-1 were found in Bacteroidetes. Based on the definition of ICE family, ICERanRCAD0179-1 was grouped in CTnDOT/ERL family; however, ICERanRCAD0133-1, which had no significant similarity with known ICEs, might be classified into a novel ICE family. The sequences of ICERanRCAD0133-1 and ICERanRCAD0179-1 were 70890 bp and 49166 bp in length, had 33.14% and 50.34% GC content, and contained 77 CDSs and 51 CDSs, respectively. Cargo genes carried by these two ICEs were predicted to encode: R-M systems, IS elements, a putative TonB-dependent receptor, a bacteriocin/ lantibiotic efflux ABC transporter, a tetracycline resistance gene and more. In addition, phylogenetic analyses revealed that ICERanRCAD0179-1 and related ICEs were derived from a common ancestor, which may have undergone divergence prior to integartation into the host bacterial chromosome, and that the core genes co-evolved via a related evolutionary process or experienced only a low degree of recombination events during spread from a common CTnDOT/ERL family ancestor. Collectively, this study is the first identification and characterization of ICEs in R. anatipestifer; and provides new insights into the genetic diversity, evolution, adaptation, antimicrobial resistance and virulence of R. anatipestifer.